Nomenclatural note on three ferns from India - Mazumdar, Jaideep (Phytotaxa, 2014)
Ongoing molecular phylogenetic analyses are continuously providing better resolution of phylogenetic relations of ferns (Ebihara et al. 2006,Tsutsumi et al. 2008) and nomenclatural changes are necessary to maintain uniformity (Christenhusz et al. 2011). Here contemporary names are suggested for three fern species from India. Type information is provided and barcodes of digitalized specimens are given.